Nanomedicine strategies for hematological malignancies: what is next?. (October 2014) - Visani, Giuseppe; Loscocco, Federica; Isidori, Alessandro
The major obstacle in treating cancer depends on the low therapeutic index of most anticancer drugs. The lack of specificity, coupled with the large volumes of distribution, translates into a nonpreferential distribution of anticancer drugs to the tumor. Accordingly, the dose of the anticancer drug that is achievable within tumor is limited, resulting in suboptimal treatment and unwanted toxicity. Nanoparticles applied as drug-delivery systems are submicron-sized (3–200 nm) particles, that can enhance the selectivity of the active drug to cancer cells through a change of its pharmacokinetic profile, while avoiding toxicity in normal cells. This review will discuss the current uses of nanodrugs in hematology, with a focus on the most promising nanoparticles in development for the treatment of hematologic tumors.